Diagnostic accuracy of machine learning-based magnetic resonance imaging models in breast cancer classification: a systematic review and meta-analysis - Jupeng Zhang; Qi Wu; Peng Lei; Xiqi Zhu; Baosheng Li (World Journal of Surgical Oncology)
Abstract Objective This meta-analysis evaluates the diagnostic accuracy of machine learning (ML)-based magnetic resonance imaging (MRI) models in distinguishing benign from malignant breast lesions and explores factors influencing their performance. Methods A systematic search of PubMed, Embase, Cochrane Library, Scopus, and Web of Science identified 12 eligible studies (from 3,739 records) up to August 2024. Data were extracted to calculate sensitivity, specificity, and area under the curve (AUC) using bivariate models in R 4.4.1. Study quality was assessed via QUADAS-2. Results Pooled sensitivity and specificity were 0.86 (95% CI: 0.82–0.90) and 0.82 (95% CI: 0.78–0.86), respectively, with an overall AUC of 0.90 (95% CI: 0.85–0.90). Diagnostic odds ratio (DOR) was 39.11 (95% CI: 25.04–53.17). Support vector machine (SVM) classifiers outperformed Naive Bayes, with higher sensitivity (0.88 vs. 0.86) and specificity (0.82 vs. 0.78). Heterogeneity was primarily attributed to MRI equipment (P = 0.037). Conclusion ML-based MRI models demonstrate high diagnostic accuracy for breast cancer classification, with pooled sensitivity of 0.86 (95% CI: 0.82–0.90), specificity of 0.82 (95% CI: 0.78–0.86), and AUC of 0.90 (95% CI: 0.85–0.90). These results support their clinical utility as screening and diagnostic adjuncts, while highlighting the need for standardized protocols to improve generalizability.